STUDI PENGUJIAN DETERIORASI (KEMUNDURAN) PADA BENIH KEDELAI - Renan Subantoro (Universitas Wahid Hasyim, 2014)
The aim of research is to study the decline of soybean seed by using a salt solution to adjust the save room humidity of 90%, 60% and 40%. Experiments using 3 x 3 factorial design arranged in a completely randomized design were repeated 4 times. The first factor is the humidity space saving seeds comprising three levels, namely: 80-90% relative humidity, relative humidity 60% and 40-50% relative humidity. The second factor is the moisture content of the seeds which consists of two levels, namely: water content of 9% and 13% moisture content. The results showed that: 1) the high humidity of disk space using KNO3 (relative humidity of 90%) accelerate the deterioration of the soybean seed. 2) high humidity disk space using KNO2 and NaBr (relative humidity of 40% and 60%) slows the deterioration in soybean seed. 3) Humidity 40% space savings and storage time 2 weeks generate power grows better than store room humidity is higher and longer storage time. Keywords: Deterioration, humidity, soybean seeds, storage